Introduction pages, NBHA-CN 53(1), 2025 - Radu E. SESTRAS (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
The papers published in Notulae Botanicae Horti Agrobotanici Cluj-Napoca, Issue 1, Volume 53, 2025, represent new exciting research in different topics of life science, respectively in plant science, horticulture, agronomy, crop science, and forestry. Among the interesting articles, we invite you to find news about: Resilience of forests in a changing climate: Responses, mechanisms, and adaptations; A panoramic review on phytochemistry, pharmacological potential, health benefits, and versatility of Solanum tuberosum L.; Role of molecular breeding in understanding salinity tolerance in cotton: limitations and perspectives; Evaluation of gas chromatography-mass spectrometry analysis and yield attributing traits of caffeine treated Trigonella corniculata L.; Induction and expression of systemic resistance to downy mildew disease in grapevine by chitosan; Molecular insights of pigeonpea sterility mosaic virus mixed infections and its variability in pigeonpea; Assessing the impact of different water stresses on physio-chemical properties and yield-related traits in tomato genotypes: Insights into stability and response; Biochemical and Raman spectroscopic insights into plant-mold interactions; Assessing genetic diversity and population structure in Tulipa species from Türkiye and Kazakhstan; Elicitation effect of hydrogen peroxide to enhance tolerance of Taxodium distichum (L.) Rich. seedlings irrigated with saline water; Effects of different rootstocks on the growth physiology and enzyme activity of Artemisia selengensis; Comparative analysis of bioactive compounds identified in the fruits of three chokeberry (Aronia melanocarpa) cultivars in different cultivation systems; The impact of cultivar and production conditions on apple quality; Biochemical attributes Portulaca oleracea as affected by manganese oxide and magnesium oxide nanoparticles; Identification of arbuscular mycorrhizal fungi in queñua (Polylepis rugulosa) in the forest of southern Peru.